2008
DOI: 10.1088/0957-4484/19/45/455603
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for preparing vertically grown single-crystalline gold nanowires

Abstract: A surfactant-free, template-less and seed-less method, namely the thermal-assisted photoreduction (TAP) process, has been developed to synthesize vertically grown Au nanowires (30-80 nm in diameter and about 2 µm in length) on the surface of thin film titanium dioxide (TiO(2)), which is locally excited by blackbody radiation. The Au nanowires thus produced are single-crystalline with a preferred [Formula: see text] growth direction. The electrical behavior investigated using a nanomanipulation device indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Similar effects have been reported for Au 20 and Cu 21 NWs synthesized by the TAP process. This phenomenon is closely related to the Honda-Fujishima effect, 25 in which electrons and holes on the surface of TiO 2 films can be excited and separated by exposure to UV light, as shown in eqn (1).…”
Section: Characteristics Of Ag Nwssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar effects have been reported for Au 20 and Cu 21 NWs synthesized by the TAP process. This phenomenon is closely related to the Honda-Fujishima effect, 25 in which electrons and holes on the surface of TiO 2 films can be excited and separated by exposure to UV light, as shown in eqn (1).…”
Section: Characteristics Of Ag Nwssupporting
confidence: 86%
“…It is well known that TiO 2 is an excellent photocatalyst when irradiated with ultraviolet (UV) light, which enables the reduction of metallic ions from solution. 18 Previous studies have shown that various face-centered cubic (FCC) metallic NWs, including Ag, 19 Au, 20 and Cu 21 could be successfully synthesized on TiO 2 films by the thermal reduction of aqueous solutions of silver nitrate (AgNO 3 ), copper chloride (CuCl 2 ), and chloroauric acid (HAuCl 4 ) respectively. In order to use Ag NWs effectively in follow-up processes, this study aims to synthesize well-aligned Ag NWs, as well as understand the mechanisms of nucleation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…They are much more successful and show some unique features in preparation, e.g., simple operation condition, diverse choices in solvents, controllable shape and size. Examples of such chemical techniques have been investigated including the so-called ‘soft’ template surfactant-directed synthesis of 1D metallic (gold and silver) nanostructures , and a DNA molecule template for gold or silver particle aggregates in conductive wires; other examples have also been demonstrated including the so-called ‘hard’ template methods such as an electrochemical method for silver nanowires using an anodic aluminum oxide (AAO) template, a polycarbonate template for silver nanowires in the ionic liquid [EMIm]PF 6 , carbon nanotubes, , and TiO 2 film , for 1D silver nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…8 The silver nanowires are particularly interesting because silver exhibits the highest electrical conductivity among all metals. Several methods have been proposed for the fabrication of silver nanowires, including the polyol process, [9][10][11][12] microwave-assisted synthesis, 13,14 solvothermal method, 15,16 wet chemical synthesis, 17 air-assisted synthesis, 18 hydrothermal methods, 19 thermal-induced methods, [20][21][22] and silver seed-assisted synthesis. 23,24 In addition to silver nanowires, copper nanowires have also been reported to be prepared by using colloidal chemical methods.…”
Section: Introductionmentioning
confidence: 99%